2019
DOI: 10.1186/s43055-019-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic efficacy of Gynecology Imaging Reporting and Data System (GI-RADS): single-center prospective cross-sectional study

Abstract: Background: To assess the validity and accuracy of GI-RADS classification in the prediction of malignancy and in triaging the management protocol in ovarian lesions.Results: One hundred fifty-six ovarian lesions were detected in the examined 116 women. The prevalence of malignant tumors was 44%. Overall GI-RADS classification rates were as follows: 41 cases (26.3%) were classified as GI-RADS 1, 26 cases (16 .7%) as GI-RADS 2, 34 cases (21.8%) as GI-RADS 3, 14 cases (8.9%) as GI-RADS 4, and 41 cases (26.3%) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
2
6
0
2
Order By: Relevance
“…In our study, color Doppler allows mapping of the blood flow within the mass and shows neovascularity in 88.7% of malignant lesions and central blood flow in 73.6% of these lesions, but 98% of the benign ovarian lesions show peripheral or absent blood flow; these results correlated well with the study done by Khurana et al [10] who reported that the detection of the blood flow has consistently related to the malignant ovarian lesions as 97.5% neovascularity could be seen in the malignant ovarian lesions. Also, our results agreed with the results of the study that was done by Barroilhet et al [4] who demonstrated that the central blood flow concerning with malignancy and the absence of blood flow or peripheral blood flow almost suggest the benignity and rolled out the malignancy as the central blood flow in their study was identified in 75.9% of the malignant ovarian lesions.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, color Doppler allows mapping of the blood flow within the mass and shows neovascularity in 88.7% of malignant lesions and central blood flow in 73.6% of these lesions, but 98% of the benign ovarian lesions show peripheral or absent blood flow; these results correlated well with the study done by Khurana et al [10] who reported that the detection of the blood flow has consistently related to the malignant ovarian lesions as 97.5% neovascularity could be seen in the malignant ovarian lesions. Also, our results agreed with the results of the study that was done by Barroilhet et al [4] who demonstrated that the central blood flow concerning with malignancy and the absence of blood flow or peripheral blood flow almost suggest the benignity and rolled out the malignancy as the central blood flow in their study was identified in 75.9% of the malignant ovarian lesions.…”
Section: Discussionsupporting
confidence: 92%
“…These results were concordant with the result of the studies done by Brown et al [15], Valentin et al [16], and Herrmann et al [17], which demonstrated that the non-hyperechoic solid component feature has long been recognized as strongly associated with malignancy in both gross pathologic and sonographic feature. Also, Khurana et al [10] reported that the papillary projections was a predictor of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations